The impact of citizen science on environmental attitudes, environmental knowledge, environmental awareness to pro–environmental citizenship behaviour - Wutthiya A. Srisathan; Kanokorn Malai; Natananan Narathawaranan; Kiadtikun Coochampoo; Phaninee Naruetharadhol (International Journal of Sustainable Engineering)
Pro-environmental behaviour is worth researching to understand the relationship between consumer behaviours and environmentally friendly consumptions. This research aims to investigate the impact of citizen science on pro-environmental citizenship behaviour when environmental attitude, environmental knowledge, and environmental awareness intermediaries in an emerging market like Thailand. The sample of 394 Thai citizens was collected from main provinces in different regions of Thailand, including Bangkok, Khon Kaen, Lamphun, and Phuket. PLS-SEM was employed to test the study hypotheses by applying the structural equation modelling approach to analyse the collected data. The main findings show that there was a positive impact of citizen science on citizen environmental attitude, citizen environmental awareness, and citizen environmental knowledge towards pro-environmental citizenship behaviour. The study also reveals that these mediated relationships play a pivotal role in translating environmental consciousness into actionable behaviours that support sustainable use and consumption. Furthermore, increased citizen environmental awareness plays a crucial role in recognising the urgency and importance of engaging in sustainable practices. Awareness acts as a catalyst, prompting individuals to reflect on their consumption patterns and lifestyle choices, ultimately leading to more environmentally friendly behaviours. Marketers may implement it with green marketing strategies by increasing more favourable to sustainable products within consumers.